Answer:
![x^(2) +y^(2)-6y-12x+43=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/trupqu62vfmevf3lwv055i5qop1g00f9rg.png)
Explanation:
The general form of the equation of a circle is given as:
where (a,b) are the centre and r is the radius.
If (5, 4) and (7, 2) are the endpoints of a diameter, we find the coordinate of the centre using the midpoint formula.
are the two points.
Midpoint of (5, 4) and (7, 2) =
![(1)/(2)(5+7 , 4+2) =(1)/(2)(12 , 6)=(6,3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/rkdb30o9jy54ns14poma3xx3c59glj8522.png)
Next, we determine the radius. Using the distance formula, we find the distance from the centre to any of the endpoints.
Distance from (5,4) to (6,3)
r=
![√((x_1-x_2)^2+(y_1-y_2)^2) \\](https://img.qammunity.org/2021/formulas/mathematics/high-school/255pz684wp7mxn6jkquj995wev6sai3u6d.png)
=
![√((5-6)^2+(4-3)^2) \\=√((-1)^2+(1)^2)=√(1+1)=√(2)\\r=√(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ms9m2xb2i8dctgi2q7aownessex2mhszfp.png)
The equation of the circle centre (6,3) with radius
is therefore given as:
![(x-a)^2+(y-b)^2=r^2\\(x-6)^2+(y-3)^2=(√(2)) ^2\\x^(2) +y^(2)-6y-12x+45=2\\x^(2) +y^(2)-6y-12x+45-2=0\\x^(2) +y^(2)-6y-12x+43=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/7qvvt7vdre10uhddq5yvgtnwl1l0ljva83.png)